2018
DOI: 10.18332/ejm/92917
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Greek women of water immersion during normal labour and birth. A qualitative study

Abstract: INTRODUCTION There is scarce information on water births in Greece, as few women labour and give birth in water. The Greek public health system does not provide water immersion as a birthing option, and so women can only experience this option in private healthcare settings. The aim of this study was to explore the key concepts and themes identified from an analysis of the experiences of women who laboured and gave birth immersed in water. METHODS This was a qualitative study involving twelve women who used wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…On entering the pool, a key benefit reported by four studies was the physical benefit of buoyancy (Antonakou et al, 2018;Gonçalves et al, 2019;McKenna & Symon, 2014;Ulfsdottir et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…On entering the pool, a key benefit reported by four studies was the physical benefit of buoyancy (Antonakou et al, 2018;Gonçalves et al, 2019;McKenna & Symon, 2014;Ulfsdottir et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Buoyancy facilitated greater freedom of movement, easeful position changes, enhanced feelings of control and contributed to women feeling as 'active participants' during their labour (Antonakou et al, 2018;Gonçalves et al, 2019;Sprague, 2004;Ulfsdottir et al, 2018). In particular, women reported unencumbered movements were valued as compared with the heaviness they had experienced throughout the later stages of pregnancy:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Waterbirth has been associated with several positive effects for women but the evidence on the benefits and potential risks has been mostly generated by observational studies. [13][14][15] A Cochrane Database systematic review published in 2018 analyzed 15 randomized controlled trials from different countries with the objective to assess the available evidence of water immersion during labor and birth. 16 The review showed that laboring in water may reduce the number of women requiring epidural analgesia (RR = 0.91; 95% CI: 0.83-0.99).…”
Section: Introductionmentioning
confidence: 99%